2019
DOI: 10.1200/jco.18.02142
|View full text |Cite
|
Sign up to set email alerts
|

Management of Cancer-Associated Anemia With Erythropoiesis-Stimulating Agents: ASCO/ASH Clinical Practice Guideline Update

Abstract: PURPOSE To update the American Society of Clinical Oncology (ASCO)/American Society of Hematology (ASH) recommendations for use of erythropoiesis-stimulating agents (ESAs) in patients with cancer. METHODS PubMed and the Cochrane Library were searched for randomized controlled trials (RCTs) and meta-analyses of RCTs in patients with cancer published from January 31, 2010, through May 14, 2018. For biosimilar ESAs, the literature search was expanded to include meta-analyses and RCTs in patients with cancer or ch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
80
0
3

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 99 publications
(90 citation statements)
references
References 46 publications
(103 reference statements)
0
80
0
3
Order By: Relevance
“…Due to the potential risks, the 2019 American Society of Clinical Oncology (ASCO)/American Society of Hematology (ASH) guidelines on management of cancer-associated anemia suggested that ESA should only be used in patients with CIA whose cancer treatment was not curative in intent and whose Hb was less than 10 g/dL. ESA should not be offered to patients whose cancer treatment was curative in intent or most patients with nonchemotherapy-induced anemia 68 .…”
Section: Epo Biology In Cancermentioning
confidence: 99%
“…Due to the potential risks, the 2019 American Society of Clinical Oncology (ASCO)/American Society of Hematology (ASH) guidelines on management of cancer-associated anemia suggested that ESA should only be used in patients with CIA whose cancer treatment was not curative in intent and whose Hb was less than 10 g/dL. ESA should not be offered to patients whose cancer treatment was curative in intent or most patients with nonchemotherapy-induced anemia 68 .…”
Section: Epo Biology In Cancermentioning
confidence: 99%
“…10 Furthermore, the American Society of Clinical Oncology (ASCO) and American Society of Hematology (ASH) guidelines for management of cancerrelated anemia recommend consideration of ESAs in patients with lower risk MDS and serum erythropoietin levels (sEPO) below 500 IU/L. 57 This is based on numerous clinical trials, which have shown increased efficacy of ESAs in lower-risk MDS patients with lower sEPO levels; in studies using an sEPO cutoff of 500 IU/L, those with lower sEPO levels had a 48-55% response rate to ESAs versus 10-16% in those with higher sEPO levels. 58 However, data suggest poor compliance with these guidelines in use of ESAs in the community.…”
Section: Erythropoiesis-simulating Agents (Esas)mentioning
confidence: 99%
“…Current FDA-approved indications for EPO include treatment of anemia associated with chronic kidney disease (CKD) or chemotherapy (40,41). The increased risk of thrombosis and stroke associated with EPO administration (39,40,(42)(43)(44) prompted researchers to design asialoerythropoietin, a desialytated version of recombinant EPO notable for its shorter half-life which allowed for its neuroprotective effects with limited effects on erythrocyte mass (45).…”
Section: Epo Derivativesmentioning
confidence: 99%